Allegory and sexual ethics in the High Middle Ages - Guynn, Noah D. (New Middle Ages (Palgrave Macmillan (Firm)), 2007)
Guynn offers an innovative new approach to the ethical, cultural, and ideological analysis of medieval allegory. Working between poststructuralism and historical materialism, he considers both the playfulness of allegory (its openness to multiple interpretations and perspectives) and its disciplinary force (the use of rhetoric to naturalize hegemonies and suppress difference and dissent). Ultimately, he argues that both tendencies can be linked to the consolidation of power within ruling class institutions and the persecution of demonized others, notably women and sexual minorities. The book examines a number of centrally canonical works, including the verse romance Eneas, Alan of Lille's De planctu Naturae, The Romance of the Rose, and the Querelle de la Rose.